The McGill-Costa Rica Project: Training in family and community medicine - Davis, M. William L. (1992)
In 1987, health authorities in Costa Rica started a training program in family and community medicine and requested assistance from the Department of Family Medicine at McGill University. The authors outline the health care system in Costa Rica and the background of the project. The design, implementation, and progress of the project to date are discussed. The problems associated with this kind of project and its future are also discussed.